Risk Attitudes and Investment Decisions across European Countries - Are Women More Conservative Investors than Men? - Dorothea Schäfer; Oleg Badunenko; Nataliya Barasinska (Verein für Socialpolitik, 2010)
This study questions the popular stereotype that women are more risk averse than men in their financial investment decisions. The analysis is based on micro-level data from large-scale surveys of private households in five European countries. In our analysis of investment decisions, we directly account for individuals' self-perceived willingness to take financial risks. The empirical evidence we provide only weakly supports the gender differences argument. We find that women are less likely to invest in risky financial assets. However, when the probability of investing is controlled for, males and females are found to allocate equal shares of their wealth to risky assets.
Keywords: G11; J16; D10; 330; gender; risk aversion; financial behavior